2018
DOI: 10.1177/0300060518762040
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sequelae of acute respiratory distress syndrome caused by severe community-acquired pneumonia: Delirium-associated cognitive impairment and post-traumatic stress disorder

Abstract: ObjectiveDelirium in critically ill patients is considered a risk factor for various long-term consequences. We evaluated delirium and associated long-term outcomes in patients with acute respiratory distress syndrome with non-H1N1 and H1N1- associated severe community-acquired pneumonia (sCAP) who had been recommended to take antiviral drugs associated with delirious symptoms as adverse effects.MethodsOf 64 patients, 42 survivors (H1N1, 15; non-H1N1, 27) were analyzed regarding the relationship between medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
(82 reference statements)
1
19
1
Order By: Relevance
“…About the impact of infections on physical function, only three studies performed objective physical and motor function tests, which targeted different physical domains (35)(36)(37). Despite the methodological heterogeneity, most studies support the hypothesis that infections impair physical function.…”
Section: Post-covid-19 Implicationsmentioning
confidence: 99%
“…About the impact of infections on physical function, only three studies performed objective physical and motor function tests, which targeted different physical domains (35)(36)(37). Despite the methodological heterogeneity, most studies support the hypothesis that infections impair physical function.…”
Section: Post-covid-19 Implicationsmentioning
confidence: 99%
“…Up to now, there have been few studies on the psychological follow-up investigation of the recovered COVID-19 patients. However, many previous studies have explored the mental health problems of patients after recovery and discharge from the hospital under a major epidemic [ [21] , [22] , [23] , [24] ]. Claudia et al [ 21 ] reported a study on cognitive abilities, post-traumatic stress disorder (PTSD), and health-related quality of life (HRQoL) in patients during follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…However, many previous studies have explored the mental health problems of patients after recovery and discharge from the hospital under a major epidemic [ [21] , [22] , [23] , [24] ]. Claudia et al [ 21 ] reported a study on cognitive abilities, post-traumatic stress disorder (PTSD), and health-related quality of life (HRQoL) in patients during follow-up. They found that survivors of severe community-acquired pneumonia and acute respiratory distress syndrome had a relatively high incidence of cognitive dysfunction, reduced functional capacity, and high incidence of PTSD that was associated with diminished HRQoL and a decreased rate of return to work.…”
Section: Introductionmentioning
confidence: 99%
“…For many people, an acute hospital admission, especially one that includes an ICU stay, results in new or worsening cognitive decline 11120121122123124. In a multicenter cohort of 821 critically ill patients with respiratory failure or shock, one in four ICU survivors, across all adult age groups, had cognitive impairment one year after discharge, equating in severity to that of having mild Alzheimer’s disease or moderate traumatic brain injury 11.…”
Section: Long Term Cognitive Impairmentmentioning
confidence: 99%